1996
DOI: 10.1177/0146167296225001
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating Procedural Fairness: Justice Becomes Both Simpler and more Complex

Abstract: Past research has indicated the importance of disputant voice in determining the fairness of conflict resolution procedures, but some conflicting data have called the role of voice into question. The authors review the role of voice in procedural fairness and conclude that some of those negative results were due to a confounded research design. In three studies, this problem was corrected, and additional data were collected. Contrary to the earlier findings, results show that when other factors are equated, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…These main eects converge with ®ndings from correlational research, where it has been Power use and dierential competence 863 observed that decision making authorities are evaluated more negatively when they do not allow say in (the process of) decision making (e.g. Folger et al, 1996;Tyler et al, 1985). In a similar vein, people generally seem less satis®ed with an autocratic leader than with a democratic one (Stitt, Schmidt, Price & Kipnis, 1983).…”
Section: Discussionsupporting
confidence: 68%
“…These main eects converge with ®ndings from correlational research, where it has been Power use and dierential competence 863 observed that decision making authorities are evaluated more negatively when they do not allow say in (the process of) decision making (e.g. Folger et al, 1996;Tyler et al, 1985). In a similar vein, people generally seem less satis®ed with an autocratic leader than with a democratic one (Stitt, Schmidt, Price & Kipnis, 1983).…”
Section: Discussionsupporting
confidence: 68%
“…We now know that a variety of conditions increase support for nonadversarial procedures. On the one hand, autocratic, inquisitorial-style procedures (with less process control than the adversarial model) are rated more favorably when they provide opportunities for voice (Sheppard, 1985;Folger, Cropanzano, Timmerman, Howes, et al, 1996), or when the conflict involves a highly volatile opponent (Morris, Leung, & Iyengar, 2004). On other hand, disputants often prefer to retain decision control (through bilateral bargaining or non-binding third-party mediation) when they have strong bargaining power, when integrative solutions are apparent, when a more adversary process threatens the disputants' ongoing relationship, or in more collectivist, communitarian cultures (see Heuer & Penrod, 1986;Leung & Lind, 1986;Leung, 1987;Lind, Huo, & Tyler, 1994;Shestowksy, 2004).…”
Section: Procedural Preferences For Dispute Resolutionmentioning
confidence: 99%
“…More recently, Folger, Cropanzano, Timmerman, Howes, and Mitchell (1996) argued that Sheppard's (1985) findings were a result of confounding the role of the third party with the voice of the disputants. The purely adversarial fourth procedure gave voice to the disputants but not to the judge (i.e., the judge could not ask questions of the disputants).…”
mentioning
confidence: 99%
“…Folger et al (1996) notwithstanding, there are at least two interrelated reasons why voice may not be directly related to procedural fairness. The first reason is that increases in voice usually come at the expense of time.…”
mentioning
confidence: 99%